Process for modifying blast furnace slag aggregate and early-strength low-shrinkage cement stabilized macadam mixture

By rapidly cooling and reheating blast furnace slag and applying nano-MgO modified fibers, the problems of shrinkage cracking and insufficient strength of cement-stabilized crushed stone mixtures and blast furnace slags have been solved, resulting in cement-stabilized crushed stone mixtures with high early strength, good later stability, and low shrinkage.

CN120864817BActive Publication Date: 2025-12-09INNER MONGOLIA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511412137.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-12-09
Estimated Expiration
2045-09-29

AI Technical Summary

Technical Problem

Existing cement-stabilized crushed stone mixtures are prone to shrinkage stress under humidity and temperature fluctuations, leading to drying shrinkage cracks and temperature shrinkage cracks. Furthermore, blast furnace slag has insufficient strength to replace natural crushed stone, resulting in limited resource utilization.

Method used

By rapidly cooling and reheating blast furnace slag, a fine crystalline structure is formed, which improves its strength and stability. Furthermore, the interwoven network structure of nano-MgO modified fibers in cement-stabilized crushed stone mixture resists shrinkage stress and promotes early strength improvement.

Benefits of technology

It effectively alleviates the shrinkage and cracking problem of cement-stabilized crushed stone mixture, improves early strength and later stability, realizes the resource utilization of blast furnace slag, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120864817B_ABST
    Figure CN120864817B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of cement-based material preparation, and particularly discloses a process for modifying blast furnace slag aggregate and early-strength low-shrinkage cement stabilized macadam mixture. The process comprises the following steps: (1) rapidly cooling slag particles discharged from a smelting furnace to room temperature to obtain pretreated slag particles; and (2) re-heating the pretreated slag particles for temperature recovery treatment, and then quickly cooling to a set temperature and slowly cooling to room temperature to obtain the modified blast furnace slag aggregate. The cement stabilized macadam mixture comprises ordinary Portland cement, sulphoaluminate cement, modified blast furnace slag aggregate, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, river sand, water reducing agent, fiber, nano MgO and mixing water. The application not only improves the hardness and stability of the blast furnace slag, but also effectively alleviates the problem of mechanical property deterioration caused by internal shrinkage and cracking of the cement stabilized macadam mixture.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of cement-based material preparation, and particularly relates to a process for modifying blast furnace slag aggregate and early-strength low-shrinkage cement stabilized macadam mixture. BACKGROUND

[0002] The information disclosed in this Background section is only for the purpose of increasing an understanding of the general background of the application and does not necessarily constitute an admission by the patent applicant or the like that the information forms part of the prior art that is already known in this field.

[0003] Cement stabilized macadam (CSM) mixture is a building material formed by adding a proper amount of cementitious material and water to macadam and then paving and compacting through the principle of embedding and extruding, and has the advantages of high strength, good stability, large rigidity, good slab body, etc. of semi-rigid base, and raw materials are easy to obtain, which is conducive to mechanized construction and can meet the needs of the development of traffic construction. At present, cement stabilized macadam mixture has been widely used in the construction of high-grade highways. However, during the strength formation and subsequent service stage, the fluctuation of the internal humidity and temperature of the cement stabilized macadam mixture will cause shrinkage stress, and when the shrinkage stress exceeds the bonding force between the internal cementitious material and the aggregate, dry shrinkage cracks and temperature shrinkage cracks will be formed, which will further expand to the surface layer of the cement stabilized macadam mixture to form reflection cracks, thereby causing destructive effects.

[0004] In addition, the aggregate for the current cement stabilized macadam mixture is mainly natural macadam, which brings a series of environmental problems during mining and production, and also faces the problem of rising costs. At the same time, a large amount of blast furnace slag produced by steel smelting also faces the problem of how to utilize it. The preparation of cement stabilized macadam by replacing natural macadam with blast furnace slag helps to utilize the blast furnace slag. However, the present inventors have found that the strength of blast furnace slag is difficult to reach the level of replacing natural macadam due to its loose and porous structure, which limits the utilization of blast furnace slag. SUMMARY

[0005] In view of the above problems, the present application provides a process for modifying blast furnace slag aggregate and early-strength low-shrinkage cement stabilized macadam mixture, which not only improves the strength and stability of blast furnace slag, but also effectively alleviates the problem of mechanical property degradation caused by internal shrinkage cracking of the cement stabilized macadam mixture. Specifically, the technical scheme of the present application is as follows.

[0006] In a first aspect, the present application provides a process for modifying blast furnace slag aggregate, comprising the following steps:

[0007] (1) rapidly cooling slag particles in a red-hot state discharged from a smelting furnace to room temperature to obtain pretreated slag particles.

[0008] (2) re-heating the pre-processed slag particles for temperature recovery treatment, and after completion, fast cooling to a set temperature, and then slow cooling to room temperature, to obtain the modified blast furnace slag aggregate.

[0009] Further, in step (1), the cooling rate of the rapid cooling is 100-300℃ / hour. Alternatively, the rapid cooling method comprises at least one of spray cooling, water cooling, etc.

[0010] Further, in step (2), the temperature recovery treatment is performed at a heating rate of 80-100℃ / hour to 800-900℃, and then holding for 1-3 hours.

[0011] Further, in step (2), the cooling rate of the fast cooling is 50-100℃ / hour, and the set temperature is 500-600℃.

[0012] Further, in step (2), the cooling rate of the slow cooling is 10-20℃ / hour.

[0013] In a first aspect, the present application provides an early-strength and low-shrinkage cement stabilized macadam mixture, which raw materials include components in the following proportions: ordinary portland cement 2.4-3.6 parts by weight, sulphoaluminate cement 3.6-7.2 parts by weight, the modified blast furnace slag aggregate described above 1596-1778 parts by weight, granulated blast furnace slag powder 76-90 parts by weight, fluorogypsum powder 20.4-30 parts by weight, carbide slag powder 3.6-6 parts by weight, river sand 502-684 parts by weight, water reducing agent 0.96-2.4 parts by weight, fiber 13-28 parts by weight, and mixing water 96-240 parts by weight.

[0014] Further, the particle size distribution of the modified blast furnace slag aggregate is between 4.75-31.5mm.

[0015] Further, the water reducing agent comprises at least one of polycarboxylic acid water reducing agent, naphthalene series water reducing agent, melamine series water reducing agent, and lignin sulfonate water reducing agent, etc.

[0016] Further, the fiber comprises at least one of polyformaldehyde fiber, polypropylene fiber, and polyacrylonitrile fiber, etc. Alternatively, the length of the fiber is 10-20mm, and the aspect ratio is 60-70.

[0017] Preferably, the fiber is a nano-MgO modified fiber obtained by the following method, comprising the following steps:

[0018] S1, performing surface plasma treatment on the cleaned and dried fiber to obtain pre-processed fiber.

[0019] S2, form a pre-modified nano-MgO dispersion liquid with nano-MgO, polyvinylpyrrolidone and anhydrous ethanol.

[0020] S3, after adjusting the system formed by silane coupling agent and ethanol-water mixture to be acidic, add the dispersion liquid, stir and react, then heat and keep warm to react. After completion, separate the solid product, wash and dry to obtain the modified nano-MgO.

[0021] S4, add the modified nano-MgO to ethanol to form a modified suspension liquid, then add the pretreated fiber, heat and keep warm to react, after completion, separate the fiber, and dry to obtain the nano-MgO modified fiber.

[0022] Further, in the step S1, the gas used in the plasma treatment includes any one of oxygen, air, etc. Optionally, the time of the plasma treatment is 120-240s. In this process, the active plasma can introduce polar oxygen-containing functional groups (including -OH, -COOH, -C=O, etc.) on the surface of the fiber and form surface etching, thereby improving the surface energy and wettability of the fiber and increasing the site density of subsequent chemical bonding and physical anchoring.

[0023] Further, in the step S2, the ratio of nano-MgO, polyvinylpyrrolidone and anhydrous ethanol is 0.8-1.3g: 0.08-0.12g: 90-100ml. In this process, the polyvinylpyrrolidone is adsorbed on the surface of nano-MgO through the carbonyl group and -Mg- site to form a polyvinylpyrrolidone adsorption layer, providing electrostatic and steric hindrance double stabilization, inhibiting particle agglomeration, and facilitating to obtain more stable and uniform MgO phase dispersion liquid.

[0024] Further, in the step S3, the volume ratio of the silane coupling agent to the ethanol-water mixture is 1:20-30. Optionally, the volume ratio of ethanol to water in the mixture is 8-10:1.

[0025] Further, in the step S3, the silane coupling agent includes at least one of KH550, KH560, KH570, etc.

[0026] Further, in the step S3, the pH of the system is adjusted to 4.5-5.5. Optionally, at least one of acetic acid, formic acid, citric acid, etc. is used to adjust the pH of the system.

[0027] Further, in the step S3, the volume ratio of the system formed by the silane coupling agent and the ethanol-water mixture to the dispersion liquid is 1:1.5-2.5. Optionally, the stirring reaction time is 25-40 min. In this process, the alkoxy groups on the silane coupling agent are first catalytically hydrolyzed to form silanol (Si-OH) in an acidic environment, and then condense with the hydroxyl groups (-Mg-OH) on the surface of the modified nano-MgO to form a stable Si-O-Mg chemical bond, and part of the silane coupling agent self-condenses to form a Si-O-Si network layer, so that the nano-MgO surface obtains a stable organic functional coating.

[0028] Further, in the step S3, the heating temperature is 60-80℃, and the reaction time is 2-3 hours. In this process, the condensation reaction of the above-mentioned silanol is further promoted, the Si-O-Mg and Si-O-Si bonding layers are densified, and the stability of the organic functional groups on the particle surface is enhanced.

[0029] Further, in the step S4, the addition amount of the modified nano-MgO in the modified suspension is 2-3 g / L. Optionally, the mass fraction of the ethanol is 80-95%.

[0030] Further, in the step S4, the heating temperature is 50-70℃, and the reaction time is 3-5 hours. In this process, the organic functional coating carried on the modified nano-MgO is used to mediate the coupling between the modified nano-MgO particles and the surface of the plasma-activated pretreated fiber.

[0031] Further, the cement stabilized macadam mixture further comprises 1.0-1.8 parts by weight of the modified nano-MgO obtained in the step S3.

[0032] Compared with the prior art, the technical scheme of the present application has at least the following beneficial effects:

[0033] (1) The present application firstly proposes a process for modifying blast furnace slag aggregate, which effectively overcomes the problem that blast furnace slag aggregate is difficult to replace natural crushed stone to prepare cement stabilized crushed stone mixture due to insufficient hardness, which is because: first, the present application rapidly cools the slag particles discharged from the smelting furnace in a high-temperature red-hot state to make them quickly pass through the high-temperature brittle zone, so that the liquid phase in the slag rapidly solidifies to form fine grain structure, which increases the specific surface area of the slag and also reduces the generation of harmful phases, because the slag contains a large amount of dense and stable mineral crystal phase of calcium feldspar, which not only has low hydration activity, but also has weak interfacial bonding ability with the cement matrix, and is easy to form a weak layer in the interfacial transition zone, and the sulfate phase contained in the slag is easy to expand in the cement hydration environment, which can cause the formation of cracks. In addition, after the slag aggregate treated by the above method is used to replace crushed stone to prepare the cement stabilized crushed stone mixture, more reaction interfaces can be provided for the hydration reaction, and the early strength can be improved. Then, the slag particles treated by the above method are subjected to temperature recovery treatment, which can eliminate the internal stress caused by the above rapid cooling and improve the stability of the slag. On the other hand, it can make the combination between the grains in the slag more closely, provide its density, and further improve the strength of the slag particles. Finally, the slag particles in high-temperature state after temperature recovery treatment are first rapidly cooled to a set temperature, and then slowly cooled to room temperature, which not only avoids the generation of cracks or structural inhomogeneity caused by rapid cooling, further stabilizes the mineral composition of the slag particles, reduces residual stress, avoids phase change, cracking or performance fluctuation in subsequent use, effectively improves the density, hardness and stability of the slag particles, not only facilitates the replacement of natural crushed stone to prepare cement stabilized crushed stone mixture, reduces production cost, but also realizes the resource utilization of blast furnace slag, a large amount of industrial solid waste.

[0034] (2) The cement stabilized crushed stone mixture of the present application also effectively alleviates the problem of strength deterioration caused by shrinkage cracking of traditional cement stabilized crushed stone mixture by using the nano-MgO modified fiber. This is because: on the one hand, the network structure formed by the interweaving and locking of the fiber distributed in the cement stabilized crushed stone mixture can effectively resist the generated shrinkage stress and reduce the generation of cracks. On the other hand, the fiber can make the modified nano-MgO more uniformly distributed in the cement stabilized crushed stone mixture, and in the process of hydration to form the expansive product magnesium hydroxide (Mg(OH)2), the fiber can constrain the expansion direction, so that the expansion stress generated by the fiber can more effectively compensate for the shrinkage and reduce the risk of cracking, rather than causing local stress concentration or damage.

[0035] (3) The modified nano-MgO has good dispersibility and is distributed in the cement stabilized macadam mixture, and the volume expansion effect provided by the expansion product formed by the hydration of the modified nano-MgO can further offset the dry shrinkage and temperature shrinkage generated in the hydration process of the cement, reduce the risk of cracks, and improve the crack resistance of the cement stabilized macadam mixture. In addition, the hydration of the modified nano-MgO effectively promotes the improvement of the early strength of the cement stabilized macadam mixture. The cement stabilized macadam mixture obtained by the method has the advantages of high early strength, stable late strength, low hydration heat, low shrinkage and good toughness. BRIEF DESCRIPTION OF DRAWINGS

[0036] The drawings constituting a part of the specification illustrate the present application and are used to further understand the present application, and do not constitute an improper limitation on the present application.

[0037] Figure 1 A modified blast furnace slag aggregate sample diagram prepared for the following Example 1.

[0038] Figure 2 A modified nano-MgO sample diagram prepared for the following Example 1.

[0039] Figure 3 A nano-MgO modified fiber sample diagram prepared for the following Example 1.

[0040] Figure 4 A modified nano-MgO sample diagram prepared for the following Example 2.

[0041] Figure 5 A nano-MgO modified fiber sample diagram prepared for the following Example 2.

[0042] Figure 6 A modified nano-MgO sample diagram prepared for the following Example 3.

[0043] Figure 7 A nano-MgO modified fiber sample diagram prepared for the following Example 3. DETAILED DESCRIPTION

[0044] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and not to limit the scope of the present application. Unless otherwise defined, all professional and scientific terms used in the present application have the same meaning as familiar to those skilled in the art. The preferred implementation methods and materials described in the present application are only used for demonstration. The technical solutions of the present application will be further described in conjunction with specific embodiments.

[0045] Example 1: A process for modifying blast furnace slag aggregate, comprising the following steps:

[0046] (1) The slag particles in red heat state at about 1500℃ discharged from the smelting furnace are sent into the spray cooling device, and then rapidly cooled to room temperature at a cooling rate of 200℃ / min to obtain pretreated slag particles.

[0047] (2) The pretreated slag particles are placed in a heating furnace, and then heated to 800℃ at a heating rate of 80℃ / h for 2 hours for re-heating treatment. After completion, the heating furnace is first cooled to 550℃ at a cooling rate of 80℃ / h, and then slowly cooled to room temperature at a cooling rate of 10℃ / h to obtain modified blast furnace slag aggregate (as shown in Figure 1 ).

[0048] 2. A method for preparing modified nano-MgO and modified fibers, comprising the following steps:

[0049] S1, The polyformaldehyde fibers (length of 20mm, aspect ratio of 60) are ultrasonically cleaned with anhydrous ethanol for 10min, then washed with clean water and dried. The obtained fibers are laid on the reaction table of the plasma treatment equipment, vacuumed to 5Pa, and then treated with oxygen for 120s to obtain pretreated fibers for standby.

[0050] S2, The nano-MgO and polyvinylpyrrolidone are added to anhydrous ethanol (the ratio of the three is 1g:0.1g:100ml), and then ultrasonically treated for 30min to obtain a dispersion liquid for standby.

[0051] S3, The silane coupling agent (KH560) and the ethanol-water mixture (formed by ethanol and water at a volume ratio of 9:1) are mixed at a volume ratio of 1:25, then acetic acid is added to adjust the pH of the system to 5, and then magnetically stirred for 30min. After completion, the dispersion liquid (volume ratio of 1:2) is added to the obtained system, and heated to 70℃ in a water bath for 2 hours of reaction. After completion, the solid product is separated by centrifugation, washed with ethanol and dried to obtain modified nano-MgO (as shown in Figure 2 ).

[0052] S4, The modified nano-MgO is added to 90% mass fraction ethanol at an addition amount of 2g / L and ultrasonically treated for 10min to obtain a modified suspension liquid, then the pretreated fibers are added and heated to 60℃ in a water bath for 4 hours of reaction. After completion, the fibers are filtered out and dried to obtain the nano-MgO modified fibers (as shown in Figure 3 ).

[0053] 3. A method for preparing early-strength low-shrinkage cement stabilized gravel mixture, comprising the following steps:

[0054] (a) The components are weighed according to the following proportions: 52.5 ordinary Portland cement 2.4 parts by weight, 42.5 high belite sulphoaluminate cement 3.6 parts by weight, modified blast furnace slag aggregate of the present embodiment 1733 parts by weight, granulated blast furnace slag powder 88.8 parts by weight, fluorogypsum powder 21.6 parts by weight, carbide slag powder 3.6 parts by weight, river sand 547 parts by weight, polycarboxylic acid water reducer 1.2 parts by weight, nano-MgO modified fiber of the present embodiment 13 parts by weight, modified nano-MgO of the present embodiment 1.2 parts by weight, and mixing water 120 parts by weight. Among them: the particle size distribution of the modified blast furnace slag aggregate is between 4.75~31.5mm, the granulated blast furnace slag powder meets the standard of S95 grade mineral powder, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0055] (b) The 52.5 ordinary Portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, and water reducing agent are added to the mixer and stirred for 2 minutes. Then the modified blast furnace slag aggregate and river sand are added and stirred for 2 minutes, and then the modified nano-MgO is added and stirred for 2 minutes. Then the mixing water is added while stirring until uniform, and finally the nano-MgO modified fiber is added and stirred for 2 minutes to obtain the cement stabilized gravel mixture.

[0056] Performance test: 1. Pour the cement stabilized gravel mixture prepared in the present embodiment into the paving equipment, set the paving thickness to 15 cm, and set the rolling thickness of each layer to 12 cm. Then wet curing for 7 days, and then natural curing for 7 days. After completion, the test piece obtained is tested for unconfined compressive strength and bending strength according to the “Highway Engineering Inorganic Binder Stabilized Material Test Specification” (JTG 3441-2024). 2. Test the fluidity of the cement stabilized gravel mixture prepared in the present embodiment according to the “Cement Mortar Fluidity Test Method” (GB / T 2419-2005). 3. Test the dry shrinkage coefficient of the cement stabilized gravel mixture prepared in the present embodiment and the average temperature shrinkage coefficient in the extreme low temperature (-25~-10℃) and extreme high temperature (45~60℃) temperature shrinkage range according to the “Highway Engineering Inorganic Binder Stabilized Material Test Specification” (JTG 3441-2024). The results are shown in the following table:

[0057]

[0058] Example 2: 1. A process for modifying blast furnace slag aggregate, comprising the following steps:

[0059] (1) The slag particles at about 1500℃ in a red-hot state discharged from the smelting furnace are sent into a spray cooling device, and then rapidly cooled to room temperature at a cooling rate of 100℃ / min to obtain pretreated slag particles.

[0060] (2) the pre-treatment slag particles are placed in a heating furnace, then heated to 850℃ at a heating rate of 90℃ / hour and kept for 3 hours for re-heating treatment, after completion, first cooled to 500℃ at a cooling rate of 50℃ / hour in the heating furnace, then slowly cooled to room temperature at a cooling rate of 10℃ / hour, thus obtaining the modified blast furnace slag aggregate, ready for use.

[0061] 2. A method for preparing modified nano-MgO and modified fiber, comprising the following steps:

[0062] S1, polypropylene fiber (length 20mm, aspect ratio 70) is cleaned with anhydrous ethanol by ultrasonic for 10min, then washed with clean water and dried. The obtained fiber is laid on the reaction table of the plasma treatment equipment, vacuumed to 5Pa, then oxygen is introduced for treatment for 200s, thus obtaining the pre-treated fiber, ready for use.

[0063] S2, nano-MgO and polyvinylpyrrolidone are added to anhydrous ethanol (the ratio of the three is 0.8g:0.08g:90ml), then ultrasonic treatment is performed for 30min, thus obtaining a dispersion liquid, ready for use.

[0064] S3, silane coupling agent (KH550) and ethanol-water mixture (formed by ethanol and water at a volume ratio of 10:1) are mixed at a volume ratio of 1:20, then acetic acid is added to adjust the pH of the system to 5.5, then magnetic stirring is performed for 40min. After completion, the dispersion liquid (volume ratio of 1:1.5) is added to the obtained system, heated to 60℃ in a water bath for 3 hours of reaction. After completion, the solid product is separated by centrifugation, washed with ethanol and dried, thus obtaining the modified nano-MgO (as shown in Figure 4 ), ready for use.

[0065] S4, the modified nano-MgO is added to 80% mass fraction ethanol at an addition amount of 2.5g / L and ultrasonic treatment is performed for 10min, thus obtaining a modified suspension liquid, then the pre-treated fiber is added, heated to 70℃ in a water bath for 3 hours of reaction, after completion, the fiber is filtered out and dried, thus obtaining the nano-MgO modified fiber (as shown in Figure 5 ), ready for use.

[0066] 3. A method for preparing early-strength low-shrinkage cement stabilized gravel mixture, comprising the following steps:

[0067] (a) The components are weighed in the following proportions: 52.5 ordinary Portland cement 3 parts by weight, 42.5 high belite sulphoaluminate cement 5 parts by weight, modified blast furnace slag aggregate of the present embodiment 1596 parts by weight, granulated blast furnace slag powder 76 parts by weight, fluorogypsum powder 20.4 parts by weight, carbide slag powder 4.8 parts by weight, river sand 502 parts by weight, polycarboxylic acid water reducing agent 0.96 parts by weight, nano-MgO modified fiber of the present embodiment 20 parts by weight, modified nano-MgO of the present embodiment 1.0 parts by weight, and mixing water 96 parts by weight. Among them: the particle size distribution of the modified blast furnace slag aggregate is between 4.75~31.5mm, the granulated blast furnace slag powder meets the standard of S95 grade powder, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0068] (b) The 52.5 ordinary Portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, and water reducing agent are added to a mixer and stirred for 2 minutes. Then the modified blast furnace slag aggregate and river sand are added and stirred for 2 minutes, and then the modified nano-MgO is added and stirred for 2 minutes. Then the mixing water is added while stirring until uniform, and finally the nano-MgO modified fiber is added and stirred for 2 minutes, to obtain the cement stabilized gravel mixture.

[0069] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient, and average temperature shrinkage coefficient of the cement stabilized gravel mixture of the present embodiment are tested by the same method as in Example 1 above, and the results are shown in the following table:

[0070]

[0071] Example 3: 1. A process for modifying blast furnace slag aggregate, comprising the following steps:

[0072] (1) The slag particles at about 1500℃ in a red-hot state discharged from the smelting furnace are sent into a spray cooling device, and then rapidly cooled to room temperature at a cooling rate of 300℃ / min to obtain pretreated slag particles.

[0073] (2) The pretreated slag particles are placed in a heating furnace, and then warmed up to 900℃ at a heating rate of 100℃ / h for 1 hour for re-warming treatment. After completion, the heating furnace is first cooled to 600℃ at a cooling rate of 100℃ / h, and then slowly cooled to room temperature at a cooling rate of 20℃ / h to obtain the modified blast furnace slag aggregate, which is ready for use.

[0074] 2. A method for preparing modified nano-MgO and modified fiber, comprising the following steps:

[0075] S1, the polyformaldehyde fiber (length 10mm, aspect ratio 60) was cleaned with anhydrous ethanol for 10min, then washed with water and dried. The obtained fiber was laid on the reaction table of the plasma treatment device, vacuumed to 5Pa, then oxygen was introduced for 240s to obtain the pretreated fiber, which was ready for use.

[0076] S2, nano-MgO, polyvinylpyrrolidone were added to anhydrous ethanol (the ratio of the three was 1.3g:0.12g:100ml) and then ultrasonic treated for 30min, and the dispersion liquid was obtained and ready for use.

[0077] S3, the silane coupling agent (KH570), ethanol-water mixture (formed by ethanol and water in a volume ratio of 8:1) were mixed in a volume ratio of 1:30, then acetic acid was added to adjust the pH of the system to 4.5, then magnetically stirred for 25min. After completion, the dispersion liquid (volume ratio of 1:2.5) was added to the obtained system, and the water bath was heated to 80℃ for 2.5h. After completion, the solid product was separated by centrifugation, washed with ethanol and dried to obtain the modified nano-MgO (as shown in Figure 6 ), ready for use.

[0078] S4, according to the addition amount of 3g / L, the modified nano-MgO was added to 95% mass fraction ethanol and ultrasonic treated for 10min to obtain the modified suspension liquid, then the pretreated fiber was added and the water bath was heated to 50℃ for 5h. After completion, the fiber was filtered out and dried to obtain the nano-MgO modified fiber (as shown in Figure 7 ), ready for use.

[0079] 3. A preparation method of early strength and low shrinkage cement stabilized macadam mixture, comprising the following steps:

[0080] (a) The components were weighed according to the following proportions: 3.6 parts by weight of 52.5 ordinary portland cement, 7.2 parts by weight of 42.5 high belite sulphoaluminate cement, 1778 parts by weight of modified blast furnace slag aggregate of the present embodiment, 90 parts by weight of granulated blast furnace slag powder, 30 parts by weight of fluorogypsum powder, 6 parts by weight of carbide slag powder, 684 parts by weight of river sand, 2.4 parts by weight of calcium lignosulfonate water reducer, 28 parts by weight of nano-MgO modified fiber of the present embodiment, 1.8 parts by weight of modified nano-MgO of the present embodiment, and 240 parts by weight of mixing water. Among them: the particle size distribution of the modified blast furnace slag aggregate is between 4.75~31.5mm, the granulated blast furnace slag powder meets the standard of S95 grade mineral powder, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0081] (b) The 52.5 ordinary portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, water reducing agent are added into the mixer and stirred for 2 min. Then the modified blast furnace slag aggregate and river sand are added and stirred for 2 min, and then the modified nano-MgO is added and stirred for 2 min, and then the mixing water is added and stirred evenly, and finally the nano-MgO modified fiber is added and stirred for 2 min, to obtain the cement stabilized gravel mixture.

[0082] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized gravel mixture of the present example are tested by the same method as that of Example 1, and the results are shown in the following table:

[0083]

[0084] Example 4: A preparation method of an early strength low shrinkage cement stabilized gravel mixture, comprising the following steps:

[0085] (1) The slag particles at about 1500℃ in a red-hot state discharged from a smelting furnace are naturally cooled to room temperature in air to obtain blast furnace slag aggregate, which is ready for use.

[0086] (2) The components are weighed according to the following proportions: 52.5 ordinary portland cement 2.4 parts by weight, 42.5 high belite sulphoaluminate cement 3.6 parts by weight, blast furnace slag aggregate of the present example 1733 parts by weight, granulated blast furnace slag powder 88.8 parts by weight, fluorogypsum powder 21.6 parts by weight, carbide slag powder 3.6 parts by weight, river sand 547 parts by weight, polycarboxylic acid water reducing agent 1.2 parts by weight, nano-MgO modified fiber prepared in Example 1 13 parts by weight, modified nano-MgO prepared in Example 1 1.2 parts by weight, and mixing water 120 parts by weight. Among them: the particle size distribution of the blast furnace slag aggregate is between 4.75~31.5mm, the granulated blast furnace slag powder meets the standard of S95 grade mineral powder, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0087] (b) The 52.5 ordinary portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, water reducing agent are added into the mixer and stirred for 2 min. Then the modified blast furnace slag aggregate and river sand are added and stirred for 2 min, and then the modified nano-MgO is added and stirred for 2 min, and then the mixing water is added and stirred evenly, and finally the nano-MgO modified fiber is added and stirred for 2 min, to obtain the cement stabilized gravel mixture.

[0088] Performance test: the same method as in Example 1 above was used to test the unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized macadam mixture of this example, and the results are shown in the following table:

[0089]

[0090] Example 5: A method for preparing an early-strength low-shrinkage cement stabilized macadam mixture, comprising the following steps:

[0091] (a) The components are weighed as follows: 3 parts by weight of 52.5 ordinary portland cement, 5 parts by weight of 42.5 high belite sulphoaluminate cement, 1596 parts by weight of pre-treated slag particles prepared in Example 2 above, 76 parts by weight of granulated blast furnace slag powder, 20.4 parts by weight of fluorogypsum powder, 4.8 parts by weight of carbide slag powder, 502 parts by weight of river sand, 0.96 parts by weight of polycarboxylic acid water reducer, 20 parts by weight of nano-MgO modified fiber in Example 2 above, 1.0 parts by weight of modified nano-MgO in Example 2 above, and 96 parts by weight of mixing water. Among them: the particle size distribution of the pre-treated slag particles is between 4.75~31.5mm, the granulated blast furnace slag powder meets the standard of S95 grade mineral powder, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0092] (b) The 52.5 ordinary portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder and water reducing agent are added to the mixer and stirred for 2 minutes. Then the pre-treated slag particles and river sand are added and stirred for 2 minutes, then the modified nano-MgO is added and stirred for 2 minutes, then the mixing water is added while stirring until uniform, and finally the nano-MgO modified fiber is added and stirred for 2 minutes to obtain the cement stabilized macadam mixture.

[0093] Performance test: the same method as in Example 1 above was used to test the unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized macadam mixture of this example, and the results are shown in the following table:

[0094]

[0095] Example 6: A method for preparing an early-strength low-shrinkage cement stabilized macadam mixture, the same as in Example 3 above, except that the modified blast furnace slag aggregate in this example is prepared as follows:

[0096] (1) The slag particles at about 1500℃ in a red-hot state discharged from the smelting furnace are sent into a spray cooling device, then cooled to room temperature at a cooling rate of 300℃ / min to obtain pre-treated slag particles.

[0097] (2) The pre-treated slag particles are placed in a heating furnace, and then heated to 900°C at a heating rate of 100°C / hour for 1 hour for re-heating treatment, and after completion, naturally cooled to room temperature in air to obtain the modified blast furnace slag aggregate.

[0098] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized gravel mixture of this embodiment are tested by the same method as in Example 1 above, and the results are shown in the following table:

[0099]

[0100] Example 7: A method for preparing an early-strength low-shrinkage cement stabilized gravel mixture, the same as in Example 2 above, except that the modified nano-MgO and modified fiber in this embodiment are prepared by the following method:

[0101] S1, ultrasonic cleaning polypropylene fiber (length 20mm, aspect ratio 70) with anhydrous ethanol for 10min, then washed with water and dried. The obtained fiber is laid on the reaction table of the plasma treatment equipment, vacuumed to 5Pa, then oxygen is introduced for 200s to obtain the pretreated fiber, ready for use.

[0102] S2, nano-MgO is added to anhydrous ethanol (the ratio of the two is 0.8g:90ml) and ultrasonic treated for 30min, and a dispersion liquid is obtained after completion, ready for use.

[0103] S3, mix silane coupling agent (KH550) and ethanol-water mixture (formed by ethanol and water in a volume ratio of 10:1) in a volume ratio of 1:20, then add acetic acid to adjust the pH of the system to 5.5, then magnetically stir for 40min. After completion, the dispersion liquid (volume ratio of 1:1.5) is added to the obtained system, and the system is heated to 60°C in a water bath for 3 hours. After completion, the solid product is separated by centrifugation, washed with ethanol and dried to obtain modified nano-MgO, ready for use.

[0104] S4, add the modified nano-MgO to 80% ethanol by mass fraction at an addition amount of 2.5g / L and ultrasonic for 10min to obtain a modified suspension liquid, then add the pretreated fiber and heat to 70°C in a water bath for 3 hours, then filter out the fiber, dry and obtain the nano-MgO modified fiber.

[0105] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized gravel mixture of this embodiment are tested by the same method as in Example 1 above, and the results are shown in the following table:

[0106]

[0107] Example 8: A method for preparing an early-strength low-shrinkage cement stabilized macadam mixture, the same as Example 1, except that the modified nano-MgO and the modified fiber in this example are prepared by the following method:

[0108] S1, the polyformaldehyde fiber (length 20mm, aspect ratio 60) is cleaned with anhydrous ethanol for 10min, then washed with water and dried. The obtained fiber is laid on the reaction table of the plasma treatment equipment, vacuumed to 5Pa, and then oxygen is introduced for treatment for 120s to obtain pretreated fiber, which is ready for use.

[0109] S2, nano-MgO and polyvinylpyrrolidone are added to anhydrous ethanol (the ratio of the three is 1g:0.1g:100ml), then ultrasonic treatment is performed for 30min, and the dispersion liquid is obtained after completion, which is ready for use.

[0110] S3, the pH of the ethanol-water mixture (formed by ethanol and water in a volume ratio of 9:1) is adjusted to 5 with acetic acid, and then magnetically stirred for 30min. After completion, the dispersion liquid is added to the obtained system, and the volume ratio of the two is 1:2. Then the obtained mixture is heated to 70℃ in a water bath for 2 hours. After completion, the solid product is separated by centrifugation, washed with ethanol and dried to obtain modified nano-MgO, which is ready for use.

[0111] S4, according to the addition amount of 2g / L, the modified nano-MgO is added to ethanol with a mass fraction of 90% and ultrasonic treatment is performed for 10min to obtain a modified suspension, then the pretreated fiber is added and heated to 60℃ in a water bath for 4 hours. After completion, the fiber is filtered out and dried to obtain the nano-MgO modified fiber.

[0112] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient and average temperature shrinkage coefficient of the cement stabilized macadam mixture of this example are tested by the same method as Example 1, and the results are shown in the following table:

[0113]

[0114] Example 9: A method for preparing an early-strength low-shrinkage cement stabilized macadam mixture, comprising the following steps:

[0115] (a) The components are weighed according to the following proportions: 52.5 ordinary Portland cement 3.6 parts by weight, 42.5 high belite sulphoaluminate cement 7.2 parts by weight, modified blast furnace slag aggregate prepared in Example 3 above 1778 parts by weight, granulated blast furnace slag powder 90 parts by weight, fluorogypsum powder 30 parts by weight, carbide slag powder 6 parts by weight, river sand 684 parts by weight, calcium lignosulfonate water reducing agent 2.4 parts by weight, polyformaldehyde fiber (length 10 mm, aspect ratio 60) 28 parts by weight, modified nano-MgO prepared in Example 3 above 1.8 parts by weight, and mixing water 240 parts by weight. Among them: the particle size distribution of the modified blast furnace slag aggregate is between 4.75~31.5 mm, the granulated blast furnace slag powder meets the S95 grade of mineral powder standard, the fineness of the fluorogypsum powder and the carbide slag powder is 300 mesh, and the river sand is medium sand.

[0116] (b) The 52.5 ordinary Portland cement, 42.5 high belite sulphoaluminate cement, granulated blast furnace slag powder, fluorogypsum powder, carbide slag powder, and water reducing agent are added to a mixer and stirred for 2 min. Then the modified blast furnace slag aggregate and river sand are added and stirred for 2 min, the modified nano-MgO is added and stirred for 2 min, then the mixing water is added while stirring until uniform, and finally the polyformaldehyde fiber is added and stirred for 2 min, to obtain the cement stabilized macadam mixture.

[0117] Performance test: The unconfined compressive strength, flexural strength test, fluidity, dry shrinkage coefficient, and average temperature shrinkage coefficient of the cement stabilized macadam mixture of the present example are tested by the same method as in Example 1 above, and the results are shown in the following table:

[0118]

[0119] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent replacements to some technical features. Any modification, equivalent replacement, improvement, etc. shall be included in the protection scope of the present application.

Claims

1. A process for modifying blast furnace slag aggregate, characterized in that, Includes the following steps: (1) The slag particles discharged from the smelting furnace are rapidly cooled to room temperature to obtain pretreated slag particles; (2) The pretreated slag particles are heated to 800-900°C at a heating rate of 80-100°C / hour and kept at that temperature for 1-3 hours for a reheating treatment. After the reheating treatment, the particles are rapidly cooled to 500-600°C at a cooling rate of 50-100°C / hour and then slowly cooled to room temperature at a cooling rate of 10-20°C / hour to obtain modified blast furnace slag aggregate.

2. The process for modifying blast furnace slag aggregate according to claim 1, characterized in that, In step (1), the cooling rate of the rapid cooling is 100~300℃ / hour.

3. The process for modifying blast furnace slag aggregate according to claim 1 or 2, characterized in that, In step (1), the rapid cooling method includes at least one of spray cooling and water cooling.

4. A high-strength, low-shrinkage cement-stabilized crushed stone mixture, characterized in that, The composition comprises the following components in the following proportions: 2.4-3.6 parts by weight of ordinary silicate cement, 3.6-7.2 parts by weight of sulfoaluminate cement, 1596-1778 parts by weight of the modified blast furnace slag aggregate obtained by the process described in any one of claims 1-3, 76-90.0 parts by weight of granulated blast furnace slag powder, 20.4-30.0 parts by weight of fluorogypsum powder, 3.6-6.0 parts by weight of calcium carbide slag powder, 502-684 parts by weight of river sand, 0.96-2.4 parts by weight of water-reducing agent, 13-28 parts by weight of fiber, 96-240 parts by weight of mixing water, and 1.0-1.8 parts by weight of modified nano-MgO; The fiber is a nano-MgO modified fiber obtained by the following method, including: S1. The cleaned and dried fibers are subjected to surface plasma treatment to obtain pretreated fibers. S2. A pre-modified nano-MgO dispersion is formed by combining nano-MgO, polyvinylpyrrolidone, and anhydrous ethanol. S3. After adjusting the system formed by the silane coupling agent and the ethanol-water mixture to acidity, add the dispersion and stir to react. Then heat and keep the reaction at the temperature. After completion, separate the solid product, wash and dry it to obtain modified nano MgO. S4. Add the modified nano-MgO to ethanol to form a modified suspension, then add the pretreated fiber and heat and keep it at a constant temperature for reaction. After the reaction is completed, separate the fiber and dry it to obtain the nano-MgO modified fiber. The modified nano-MgO is obtained from steps S1 to S3.

5. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, The modified blast furnace slag aggregate has a particle size distribution between 4.75 and 31.5 mm.

6. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, The water-reducing agent includes at least one of the following: polycarboxylate water-reducing agent, naphthalene-based water-reducing agent, melamine-based water-reducing agent, and lignin sulfonate water-reducing agent.

7. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, The fibers include at least one of the following: polyoxymethylene fiber, polyethylene fiber, polypropylene fiber, and polyacrylonitrile fiber.

8. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, The fiber has a length of 10-20 mm and an aspect ratio of 60-70.

9. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S1, the gas used for plasma treatment includes either oxygen or air.

10. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S1, the plasma treatment time is 120~240s.

11. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S2, the ratio of nano-MgO, polyvinylpyrrolidone, and anhydrous ethanol is 0.8~1.3g: 0.08~0.12g: 90~100ml.

12. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the volume ratio of the silane coupling agent to the ethanol-water mixture is 1:20~30.

13. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the volume ratio of ethanol to water in the mixture is 8~10:

1.

14. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the silane coupling agent includes at least one of KH550, KH560, and KH570.

15. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the pH of the system is adjusted to 4.5~5.

5.

16. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the volume ratio of the system formed by the silane coupling agent and the ethanol-water mixture to the dispersion is 1:1.5~2.

5.

17. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the stirring reaction time is 25-40 minutes.

18. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, at least one of acetic acid, formic acid, and citric acid is used to adjust the pH of the system.

19. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S3, the heating and heat preservation temperature is 60~80℃, and the reaction time is 2~3 hours.

20. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S4, the amount of modified nano-MgO added to the modified suspension is 2 g / L.

21. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to claim 4, characterized in that, In step S4, the mass fraction of the ethanol is 80-95%.

22. The early-strength, low-shrinkage cement-stabilized crushed stone mixture according to any one of claims 4-21, characterized in that, In step S4, the heating and heat preservation temperature is 50~70℃, and the reaction time is 3~5 hours.

Citation Information

Patent Citations

  • Preparation process for preparing granulated material from blast furnace slag powder

    CN110981243A

  • Low-shrinkage alkali-activated cementing material and preparation method thereof

    CN116589233A